Response force as a measure of stimuli context impact on simple reaction time - Ivanec, Dragutin (Array, 2002)
Mean reaction time is slower when stimuli are presented randomly in mixed blocks, than when they are presented in pure blocks. It is possible to explain such contextual effects by Grices model of variable criterion variation, or by Adaptation-Level Theory proposed by Helson. However, both of the models are insufficient in explaining all outcomes in sensori-motor procesess conected with type of stimuli presentation. The aim of the study was to offer additional proof for the nature of stimuli context impact on simple reaction time. We, therefore, used reaction force as an additional measure of different processes in two contextual situation. Reaction force is closely connected with intensity of stimulus - stronger stimuli produce stronger reaction force. Otherwise, reaction time and reaction force were not associated when every single reaction was observed. According to this findings, reaction force can be very useful variable in studing processes connected with contextual impact on simple reaction time. The study was conducted on 18 subjects. All subjects were exposed to both experimental conditions ; condition with stimuli presented in mixed blocks and condition with same stimulus intensity in sequence (pure blocks). The reaction time and response force were measured. As expected, the results showed for mean reaction time to depend on stimuli context. In mixed blocks condition the reaction time was found to be longer. The reaction force was not associated with the stimuli context and was found to be the same in both experimental conditions. According to this relation of context stimuli, reaction time and reaction force, context stimuli influences reaction time, neither through perceptive, nor motor processes. Cognitive, central processes seem to play major role.